If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 3)(x + -3)(2x + 1) = 0 Reorder the terms: (3 + x)(x + -3)(2x + 1) = 0 Reorder the terms: (3 + x)(-3 + x)(2x + 1) = 0 Reorder the terms: (3 + x)(-3 + x)(1 + 2x) = 0 Multiply (3 + x) * (-3 + x) (3(-3 + x) + x(-3 + x))(1 + 2x) = 0 ((-3 * 3 + x * 3) + x(-3 + x))(1 + 2x) = 0 ((-9 + 3x) + x(-3 + x))(1 + 2x) = 0 (-9 + 3x + (-3 * x + x * x))(1 + 2x) = 0 (-9 + 3x + (-3x + x2))(1 + 2x) = 0 Combine like terms: 3x + -3x = 0 (-9 + 0 + x2)(1 + 2x) = 0 (-9 + x2)(1 + 2x) = 0 Multiply (-9 + x2) * (1 + 2x) (-9(1 + 2x) + x2(1 + 2x)) = 0 ((1 * -9 + 2x * -9) + x2(1 + 2x)) = 0 ((-9 + -18x) + x2(1 + 2x)) = 0 (-9 + -18x + (1 * x2 + 2x * x2)) = 0 (-9 + -18x + (1x2 + 2x3)) = 0 (-9 + -18x + 1x2 + 2x3) = 0 Solving -9 + -18x + 1x2 + 2x3 = 0 Solving for variable 'x'. The solution to this equation could not be determined.
| -91+6x=-10x+133 | | 1/2(4x-6)=7 | | [-15(-1.5)]+[(-2.5)*1.25]= | | [-15(-15)]+[(-2.5)*1.25]= | | 25x^2-18x-200=0 | | 2x^5+17x^4+45x^3+28x^2-44x+48=0 | | 0.67x=18 | | 2(x-2)=x+14 | | 0.75z-1=0.25z+2 | | 0.01x-3=4 | | 0.3x-5=0.1x+3 | | -0.25x=-5 | | -0.25=-5 | | 1/4(8x-24) | | q=1000-.4p | | 3x(3xy-5y)= | | 6-(5x/2(7-3x)/2 | | -4=0.4x | | 8(x-2)=7(x-1)-12+x | | 0.15x+27=31.5 | | 3x-17=52 | | (x-5)(2x-14)=4(3x-21) | | p^4/p^3 | | -7n(-1+3a)=5(3-5a) | | 20-5x=75 | | 0/x=2 | | x=345/2 | | 3x=3(x-7)+12 | | 33.75=9.75xY | | 2(2-0.3x)=14 | | 30X+15Y=8400 | | 1 = r4– 3 |